2001
DOI: 10.1007/s005350170003
|View full text |Cite
|
Sign up to set email alerts
|

Association between Helicobacter pylori infection and the risk of gastric cancer in the Korean population: prospective case-controlled study

Abstract: H. pylori infection may be one of the important risk factors for the development of gastric cancer in Korea, an area of high prevalence of H. pylori infection and a high incidence of gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 31 publications
3
15
0
Order By: Relevance
“…This PAF is very similar to that reported by Parkin [45]. For the sensitivity analysis, a meta-analysis was conducted for the summary risk measures from four case-control studies conducted in the Korean population with regard to the association between H. pylori and gastric cancer risk [17][18][19][20]. When the pooled RR of 1.69 from the Korean studies was applied, the PAFs due to H. pylori were 36.44% in men and 34.25% in women.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…This PAF is very similar to that reported by Parkin [45]. For the sensitivity analysis, a meta-analysis was conducted for the summary risk measures from four case-control studies conducted in the Korean population with regard to the association between H. pylori and gastric cancer risk [17][18][19][20]. When the pooled RR of 1.69 from the Korean studies was applied, the PAFs due to H. pylori were 36.44% in men and 34.25% in women.…”
Section: Resultssupporting
confidence: 73%
“…We adopted the RR of 5.9 from the international metaanalysis of nested case-control studies for the current analysis [16] because four Korean studies had a case-control design [17][18][19][20] (supplemental Table 2 and Figure 1a and 1b, available at Annals of Oncology online). In addition, a matched OR of 6.3 from a nested case-control study of the association between H. pylori and gastric MALT lymphoma within an American cohort was adopted for the current analysis [21].…”
Section: Relative Risk Of Cancers and Infectious Agentsmentioning
confidence: 99%
“…However, previous studies have shown the association between lower education and a high prevalence of H. pylori . [138] We recruited participants from the city of Pune but not from the nearby villages, and none of the participants in our study was uneducated. We came across a significant amount of missing data for the quantification of cigarettes and alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Since Virchow proposed that chronic inflammation promotes carcinogenesis, accumulating studies support the hypothesis that chronic inflammations increase the risk of cancer development (18)(19)(20)(21). Microbial infections, autoimmune disease, and inflammatory conditions of unknown origin are recognized as triggers of chronic inflammation related with cancer development, as well as the association of Helicobacter pylori (H. pylori) with gastric cancer and gastric mucosal lymphoma (18,19,22). Because a detailed histology of dissected regional LNs other than absence of tumor involvement is not obtained in this study, information as to the infection with H. pylori of the resected gastric specimens or regional LNs in gastric cancer patients is not available.…”
Section: Discussionmentioning
confidence: 99%